Consumer Protection for The Hacking of Personal Data of Tokopedia Marketplace Users - Taffarel Almeyda, Ivan; Prasetyawati, Endang (CV. Era Digital Nusantara, 2024)
The issue of consumer personal data security that is vulnerable to hacking and misuse by irresponsible parties should be the main focus of the government through the establishment of Law Number 27 of 2022 concerning Personal Data Protection. The subject matter of this research is a case that occurred in Tokopedia e-commerce. Concerns about personal data security and privacy arose as a result of a data leak that occurred in May 2020, in which the data of 91 million Tokopedia user accounts were hacked and offered for sale on the Dark Web. From a sociological point of view, this event has the potential to reduce public trust in e-commerce platforms and digital technology as a whole. When data is leaked, consumers may become more wary and potentially reduce interest in online shopping for fear that their personal data will be stolen or misused. The subject matter of this research is how legal protection efforts can be provided against consumer personal data leaks in the Tokopedia Marketplace with a normative legal research method, also known as normative juridical research, will be employed in this study. The normative juridical research approach involves doing legal study solely through the examination of secondary data or library materials. Normative juridical research, sometimes known as the normative legal research method, is the approach method used in this writing. Library legal research using secondary data or library materials is known as normative juridical research.